Common Foreign, Security, and Defense Policies - Mikos-Sitek, Agnieszka (The Policies of the European Union from a Central European Perspective, 2022)
This chapter examines the issue of the common foreign and security policy, as well as its integral part of the common security and defense policy, discussed from the perspective of the EU Member States, including, in particular, the countries of Central and Eastern Europe. To create a substantive basis for the assessment of the position of EU Member States in the CSFP implementation process, the basic issues related to the provisions of the treaties in this area are discussed at the beginning. An important element of the chapter is also the characterization and identification of the separateness of the regulations in force in the field of CFSP. Attention is also paid to institutional solutions, which are important in this case, as well as legal instruments for the implementation of CFSP. In addition to general guidelines, decisions, and the issues of strengthening systematic cooperation, attention is also drawn to the importance of international agreements concluded by the EU in the area of CFSP. An important element of the analysis of the rights and obligations of EU Member States is also the decision-making procedure considering the unanimity principle, as well as the so-called solidarity clauses. The discussion of the role and position of the EU Member State in the CFSP area is summarized with a reference to issues that specifically concern the countries of Central and Eastern Europe. Attention is drawn to the spectrum of problems that arise in the practice of CFSP implementation, related primarily to significant differences in defining state security guarantees and the underlying factors. Keywords: Common foreign and security policy, common security and defense policy, EU external action, EU Member State, Central and Eastern Europe, unanimity mechanism, general guidelines, action decisions, position decisions